Antiplatelet agents and proton pump inhibitors – personalizing treatment - Eugene Lin; Rajiv Padmanabhan; Majaz Moonis (Dove Medical Press, 2010)
Eugene Lin, Rajiv Padmanabhan, Majaz MoonisDepartment of Neurology, University of Massachusetts Medical School and UMass Memorial Medical Center, Worcester, Massachusetts, USAIntroduction: Antiplatelet therapy remains one of the cornerstones in the management of noncardioembolic ischemic stroke. However, a significant percentage of patients have concomitant gastroesophageal reflux or peptic ulcer disease that requires acid-reducing medications, the most powerful and effective being the proton pump inhibitors (PPIs). Antiplatelet efficacy, at least in vivo, and particularly for clopidogrel, has been shown to be reduced with concomitant proton pump inhibitor use. Whether this is clinically relevant is not clear from the limited studies available.Methods: We conducted an extensive review of studies available on Medline related to pharmacodynamic interactions between the antiplatelet medications and proton pump inhibitors as well as clinical studies that addressed this potential interaction.Results: Based on the present pharmacodynamic and clinical studies we did not find a significant interaction that would reduce the efficacy of antiplatelet agents with concomitant user of proton pump inhibitors.Conclusions: Patients on antiplatelet agents after a transient ischemic attack or ischemic stroke can safely use aspirin, and extended release dipyridamole/aspirin with proton pump inhibitors. Patients on clopidogrel may use other acid-reducing drugs besides proton pump inhibitors. In rare cases where proton pump inhibitors and clopidogrel have to be used concurrently, careful close monitoring for recurrent vascular events is required.Keywords: proton pump inhibitors, antiplatelet medications, clopidogrel, ischemic stroke, cardiovascular events